1997
DOI: 10.1063/1.365939
|View full text |Cite
|
Sign up to set email alerts
|

High intensity illumination effects in LiNbO3 and KTiOPO4 waveguides

Abstract: Quasi-phase-matched waveguides are known to degrade when generating high intensity short wavelength light. Photoinduced changes in the refractive indices can lead to reduced efficiency by broadening phase-matching curves or inducing power dependent losses. In this work a pump-probe technique was used to investigate photorefractive effects in nonlinear optical waveguides. A strong two photon photorefractive effect in single domain and Ti-poled LiNbO3 was found that is considerably reduced in electric field peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Thereafter, the SH power shows significant fluctuations. These are related to the photorefractive effect, [7][8][9][10][11][12] which cannot only change the efficiency of SHG but also increase noise in the SH wave.…”
Section: Shg With 532 Nm Irradiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Thereafter, the SH power shows significant fluctuations. These are related to the photorefractive effect, [7][8][9][10][11][12] which cannot only change the efficiency of SHG but also increase noise in the SH wave.…”
Section: Shg With 532 Nm Irradiationmentioning
confidence: 99%
“…Therefore, high-power light sources (up to ∼200 mW) are required to achieve efficient conversions in many practical applications [6,7]. It has been found that LiNbO 3 waveguides are more vulnerable to high-power irradiating light than bulk crystals, especially to lightwave with a shorter wavelength, due to the photorefractive effect (PRE) [7][8][9][10][11][12]. In addition, in both bulk and waveguide PPLN crystals, the phase-matching conditions are influenced by the temperature distribution along the optical path of the interacting wave; and high-power irradiation is apt to generate uneven temperature distribution [2, 7, 13].…”
Section: Introductionmentioning
confidence: 99%
“…A photovoltaic current will flow because of the noncentrosymmetric structure of the crystal. This space charge field will lead to a change of the refractive index due to the electro optical effect [52]. Photo-refraction causes a QPM wavelength shift, degradation of the SH output power and can lead to severe beam distortions.…”
Section: Limitations and Damage Mechanismsmentioning
confidence: 99%
“…Although photo-refractive effects are reduced by the poling process itself compared to single domain crystals [52], it still has a huge impact on the performance of QPM devices.…”
Section: Limitations and Damage Mechanismsmentioning
confidence: 99%
“…There are, however, a number of reasons to do so. High-squeezing experiments have been carried out in bulk KTP and PPKTP [3,4]; KTP has a high damage threshold, a low amount of green-induced IR absorption [19,20], low-temperature sensitivity [21,22], and no significant photorefraction damage [23]. All this makes KTP a very promising material for nonlinear optical waveguide applications.…”
mentioning
confidence: 99%